2020
DOI: 10.1155/2020/8352176
|View full text |Cite
|
Sign up to set email alerts
|

Wuqinxi Exercise Improves Hand Dexterity in Patients with Parkinson’s Disease

Abstract: Objective. This study was designed to evaluate the effect of Wuqinxi after one session and 12-week intervention on hand dexterity in patients with Parkinson’s disease (PD). Methods. Forty-six elderly participants with mild-to-moderate PD were randomly assigned to the groups trained with Wuqinxi (n = 23) or stretching (n = 23). All participants practiced 60 min session of either of these exercises, 2 sessions a week for 12 weeks in standing position. The score of Purdue Pegboard Test (PPT) and time for Soda Pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Additionally, participants in the experimental group improved their mentation, behavior, and mood (as assessed using UPDRS I) after the archery intervention, suggesting that practicing the archery exercise may have the potential to induce joyful feelings or even self-fulfillment feelings in patients with PD who succeeded in shooting the target point repeatedly, which in turn decreased their depressive symptoms. It is worth noting that similar to other complementary approaches such as Wuqinxi exercise [ 32 , 33 ], yoga [ 34 ], and active theatre [ 36 , 37 ], the archery approach also helps to improve psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, participants in the experimental group improved their mentation, behavior, and mood (as assessed using UPDRS I) after the archery intervention, suggesting that practicing the archery exercise may have the potential to induce joyful feelings or even self-fulfillment feelings in patients with PD who succeeded in shooting the target point repeatedly, which in turn decreased their depressive symptoms. It is worth noting that similar to other complementary approaches such as Wuqinxi exercise [ 32 , 33 ], yoga [ 34 ], and active theatre [ 36 , 37 ], the archery approach also helps to improve psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the usual exercise interventions described above, Qigong [ 29 , 30 ], Tai Chi [ 31 ], Wuqinxi [ 32 , 33 ], yoga [ 34 ], Irish set dancing [ 35 ], active theatre therapy [ 36 , 37 ], and archery [ 15 ] were proposed as complementary therapeutic methods for improving the motor function of patients with PD, and empirical evidence showed more or less favorable effects not only on motor function but also on psychological well-being (e.g., the reduction in depression, apathy, and anxiety). Although archery training was much less applied, it appeared to be a promising approach for improving upper extremity functions.…”
Section: Introductionmentioning
confidence: 99%
“…Given that there has not been any previous TMS study examining cortical connectivity in people with PD after a Wu Qin Xi exercise intervention, we estimated the required sample size based on the number of subjects included in a previous behavioral experimental study ( 29 ). A power analysis in G * power software indicated that 63 participants (21/group) will be required to demonstrate effects on primary and secondary outcomes with repeated-measures analyses of variance (ANOVAs) at a 0.05 significance level and 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…16 A 12wk Qigong exercise imitating five animal movements could improve the PPT scores of dominant hand, both hands, and assembly subtests as compared with stretching exercise in people with mild to moderate PD. After training, better manual dexterity was accompanied by significant improvement in activities of daily living (ADLs) and emotional well-being domain subscores of the Parkinson Disease Questionnaire (PDQ-39) in both groups, 17 implying possible correlations between hand functions with HRQoL. Thus, further investigation is needed to establish the associations between manual dexterity and grip strength with self-perceived hand functions and HRQoL, while considering the MAH and hand dominance.…”
Section: What Is Newmentioning
confidence: 99%